Parmenides as a Thinker of Fate - Torrijos Castrillejo, David (Religions, 2024)
Although some ancient sources relate Parmenides to the religious doctrine of fate, this concept is not usually prominent in the scholarly presentation of the Eleatic thinker. Here, we offer a tentative interpretation of the notion of necessity in Parmenides’ poem, as a peculiar philosophical understanding of the presence of fate in reality. Necessity, divinised by Parmenides, implies that all things are bound together by the chains of fate. Therefore, his philosophical proposal consists in understanding this unity of reality originated by the connexion of fatal necessity. However, this presence of fate in all things is not bad news, but also means that everything is connected by Love.